ANALYSIS IMPLEMENTATION OF BACK REFERRAL PROGRAM DIABETES MELLITUS AND HYPERTENSION IN HOSPITAL X, JAKARTA - Ambari, Riza; Savitri, Mieke (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: Since morbidity rate of Diabetes Mellitus and Hypertension in Indonesia increased, the number of referral in hospital automatically high. National Health Insurance and hospital burden also increase if the Back- Referral Program (BRP) has not been implemented yet. The impact of the ineffectiveness of Back-Referral Program also felt by Hospital